Synthesis and characterization of functionalized Se-MCM-41 a new drug carrier mesopore composite - Rahman, Md. Mokhlesur; Yusof, Alias Mohd; Yusan, Sabrie; Ansary , Rezaul H. (2014)

(untitled)
Various nanocomposite materials play a number of important roles in modern science and technology including pharmaceutical science. Among these materials, mesoporous materials cover a large number of applications in drug delivery system. Mesoporous Se-MCM‐41 is one of the mesoporous materials used nowadays as a drug carrier. The quantitative incorporation and high dispersion of selenium nanoparticles into MCM-41 has been made possible by the coordination between Se (IV) ion and APTES-anchored MCM-41. The samples were characterized by X-ray powder diffraction, Fourier-transformed infrared spectroscopy (FTIR), scanning electron microscopy (SEM), nitrogen adsorption–desorption via multi point Brunauer, Emmett and Teller (BET) analysis, Raman spectroscopy and UV-Vis diffusion reflection spectroscopy (UV-vis/DRS). X-ray diffraction patterns indicated the existence of the synthesized Se nanoparticles as a crystalline structure with the functionalized material retaining the standard MCM-41 structure. Results from FTIR and Raman spectroscopy demonstrated that the Se and amino groups are incorporated into the Si–O framework. Nitrogen adsorption was used to determine specific surface area, pore diameter and pore volume in the MCM-41 and Se-MCM-41 mesoporous molecular sieves. The increase in cell parameter and the decrease in surface area observed by N2 adsorption–desorption technique were taken as evidence of selenium introduction inside the MCM-41 framework. The presence of a strong absorption band centered at ca. 210 nm in the diffused reflectance UV–vis spectra could explain the presence of hexagonal selenium in the silica network.